Penegakan Hukum Bagi Pelaku Tindak Pidana Skimming Oleh Warga Negara Asing Berdasarkan UU ITE - Adib Yanuar Gunawan; H. Sutrisno (Universitas Sains dan Teknologi Komputer, 2023)
The purpose of this thesis is to investigate and analyze Law Enforcement for Foreign Nationals Engaging in Skimming Crimes Based on the ITE Law and the Challenges and Efforts Encountered by the East Java Regional Police in Enforcing Skimming Criminal Law. This research employs a legal research approach with a Juridical-Empirical method, utilizing qualitative data analysis based on data collected through field observations, legal studies, legal literature, and interviews.Based on the research conducted between 2020 and 2022, the SubDit V Ditreskrimsus of the East Java Regional Police successfully handled three skimming cases within the East Java region in accordance with relevant legislation, such as Law Number 19 of 2016 and the Criminal Code. The relevant articles were used as the legal basis for prosecuting individuals involved in skimming crimes. The East Java Regional Police faced challenges such as language barriers with the perpetrators and the notification of their families or embassies. These challenges were addressed by Ditreskrimsus through the Implementation Guidelines for Criminal Investigation Management. Proactive efforts included disseminating information through social media, video tron, webinars, and YouTube, along with the pursuit of individuals who were still on the wanted list. These measures aimed to reduce skimming victims and enhance law enforcement in East Java.